Apical Hypertrophic Cardiomyopathy in Association with PulmonaryArtery Hypertension - Mehdi Peighambari (Journal of Cardiovascular and Thoracic Research, 2012)
Apical Hypertrophic Cardiomyopathy is an uncommon condition constituting 1% -2% of the cases with Hypertrophic Cardiomyopathy (HCM) diagnosis. We interestingly report two patients with apical hypertrophic cardiomyopathy in association with significant pulmonary artery hypertension without any other underlying reason for pulmonary hypertension. The patients were assessed by echocardiography, cardiac catheterization and pulmonary function parameters study.